Comparison of Prenatal, Perinatal, and Postnatal Knowledge Levels of Pregnant Women and Their Distress Conditions - Dzhevriye Emir; Hatice Sütçü (Galenos Publishing House, 2023)
Objective:This research is a descriptive study conducted to investigate and compare the knowledge levels of pregnant women about pregnancy, childbirth and postpartum, and their distress.Method:The sample of the study consisted of 178 pregnant women who applied to the obstetrics and gynecology polyclinic of a state hospital in Northern Cyprus, and the data were collected between January 1 and April 1, 2019. Data were collected through forms, which included the "Tilburg pregnancy distress scale (TPDS)", the "knowledge questions about pregnancy, birth, and postpartum" and socio-demographic and obstetric information of participants.Results:The average number of right answers by pregnant women to the "knowledge questions about pregnancy, birth and postpartum" was 18.0±4.0 (3-26) out of a total of 32 items, indicating that pregnant women in Northern Cyprus had medium knowledge level on these issues. In addition, the average score for "TPDS was 13.6±6.7, out of a total of pregnant women participating in the study. The subscale, "TPDS" "partner involvement", "negative effect", and general scale scores are lower than the sub-limits determined for distress definition. Finally, it was observed that there is no relationship between the distress status and the level of knowledge by pregnant women (p>0.05).Conclusion:The results of this study show that there is no relationship between the knowledge levels of pregnant women and their pregnancy-related distress.